The Effect of Addition of Shallot (Allium ascalonicum L.) Peel Flour as a Feed Additive on Antibacterial Activity and Characteristics of Small Intestine of Broiler - Kurniawan, Muhammad Iqbal; Sjofjan, Osfar; Tistiana, Heli (Journal of Agriprecision & Social Impact, 2025)
Feed is the most important factor in broiler farming to achieve optimal productivity, because feed costs reach 60-70% of the total production costs, therefore the quantity and quality of feed need to be considered. Efforts that can be made to increase feed efficiency and reduce production costs in broiler farming businesses are by adding feed additives. This study aims to evaluate the effect of adding shallot peel flour as a feed additive on antibacterial activity and characteristics of broiler intestines. The method used in this study is a laboratory analysis method and a field experimental method designed using a Completely Randomized Design (CRD) with 6 treatments and 5 replications. The results showed that the treatment of adding red shallot peel flour as a feed additive gave a very significant difference (P <0.01) on the pH, viscosity, length of villi and surface area of the villi of the small intestine of broiler, but gave no significant difference (P>0.05) on the number of villi and depth of the crypts of the small intestine of broiler. The conclusion of this study is that the addition of red shallot peel flour with a level of 1% as an additive in feed gives the best results in improving the characteristics of the small intestine of broiler.